Arsenophonus and Sodalis replacements shape evolution of symbiosis in louse flies - Šochová, Eva; Husník, Filip; Nováková, Eva; Halajian, Ali; Hypša, Václav (PeerJ, 2017)
Symbiotic interactions between insects and bacteria are ubiquitous and form a continuum from loose facultative symbiosis to greatly intimate and stable obligate symbiosis. In blood-sucking insects living exclusively on vertebrate blood, obligate endosymbionts are essential for hosts and hypothesized to supplement B-vitamins and cofactors missing from their blood diet. The role and distribution of facultative endosymbionts and their evolutionary significance as seeds of obligate symbioses are much less understood. Here, using phylogenetic approaches, we focus on the Hippoboscidae phylogeny as well as the stability and dynamics of obligate symbioses within this bloodsucking group. In particular, we demonstrate a new potentially obligate lineage of Sodalis co-evolving with the Olfersini subclade of Hippoboscidae. We also show several likely facultative Sodalis lineages closely related to Sodalis praecaptivus (HS strain) and suggest repeated acquisition of novel symbionts from the environment. Similar to Sodalis, Arsenophonus endosymbionts also form both obligate endosymbiotic lineages co-evolving with their hosts (Ornithomyini and Ornithoica groups) as well as possibly facultative infections incongruent with the Hippoboscidae phylogeny. Finally, we reveal substantial diversity of Wolbachia strains detected in Hippoboscidae samples falling into three supergroups: A, B, and the most common F. Altogether, our results prove the associations between Hippoboscoidea and their symbiotic bacteria to undergo surprisingly dynamic, yet selective, evolutionary processes strongly shaped by repeated endosymbiont replacements. Interestingly, obligate symbionts only originate from two endosymbiont genera, Arsenophonus and Sodalis, suggesting that the host is either highly selective about its future obligate symbionts or that these two lineages are the most competitive when establishing symbioses in louse flies.
Keywords: Sodalis; Phylogeny; Arsenophonus; Wolbachia; Replacements; Louse flies